Pengaruh Penambahan Electrical Myostimulation (Ems) Dan Latihan Hurdle Hops Terhadap Tinggi Lompatan Pada Pemain Bola Voli - Pamungkas, Kejora Puteri, Totok Budi Santoso, S.Fis, MPH (2016)
Background: One of the factors that support an athlete's performance level of volleyball is a leg muscle power, which can be trained through an exercise program. EMS is a physiotherapy modalities that uses electrical currents that can cause one or certain muscle groups are stimulated to contract. Muscle contractions with the addition of lectrical Myostimulation use can increase muscle strength. Hurdle hops exercise are essentially a form of exercise that also train the muscles of the leg. Physiotherapist program are given in volleyball athletes in increasing the height of the jump include electrical myostimulation and hurdle hops exercise. Objective: This study aimed to determine the effect of electrical myostimulation and a high hurdle hops exercise to the high of volleyball players jump. Methods: The research method using a quasi-experimental research design with pre and post test with two group design. The samples used were 20 people. Results: Statistical tests using Wilcoxon and Mann-Whitney test with the results there are effect of adding electrical myostimulation and hurdle hops exercise to the increase in height of the jump in volleyball players with a data value group 1 of Wilcoxon p = 0.05 (<0.05) and group 2 of Wilcoxon p = 0.07 (<0.05). As for the influence of different test p value = 0.00 (<0.05). Conclusion: With these results we can conclude there is the influence of group 1 and group 2 but the results are better in group 1 with the addition of electrical myostimulation and hurdle hops exercise to increase the height of the jump in volleyball players.